Nitrogen-doped mesoporous graphene nanoflakes for high performance ionic liquid supercapacitors. (1st September 2020) - Arkhipova, Ekaterina A.; Ivanov, Anton S.; Maslakov, Konstantin I.; Savilov, Serguei V.
Abstract: Mesoporous nitrogen-doped graphene nanoflakes (N-GNFs) with high nitrogen doping level of 5.0–10.7 at.% were produced by a facile template CVD synthesis using the mixture of acetonitrile and benzene as a precursor. The pore structure, morphology and physicochemical properties of N-GNFs were characterized by TEM, XPS, Raman spectroscopy, and low-temperature nitrogen physisorption. The electrochemical performance of N-GNFs was tested in electric double-layer capacitor (EDLC) with ionic liquid electrolyte (1.2 M N + Et4 TFSI − solution in CH3 CN) by cyclic voltammetry, galvanostatic charge-discharge measurements, and electrochemical impedance spectroscopy. With increasing the nitrogen content in N-GNFs their specific capacitance increased and achieved 167 F g −1  at a scan rate of 5 mV s −1 . The maximum delivered energy density was 46.3 Wh kg −1, which corresponded to a power density of 0.74 kW kg −1 . The high electrochemical performance of N-GNFs was attributed both to the pseudo-capacitance of active nitrogen sites and to the developed mesoporosity. Different tetraalkylammonium bis(trifluoromethylsulfonyl)imide ionic liquids were used to evaluate the cation size effect on the stability and performance of N-GNFs-based EDLCs. In contrast to N + Et4 TFSI − and N + Bu4 TFSI − electrolytes, the cycling performance of N-GNFs in N + Me4 TFSI − was limited because of the electrode degradation resulted from the intercalation of N + Me4 ions between graphene layers and their exfoliation. Graphical abstract: Image 1 Highlights: EDLC electrodes from mesoporous nitrogen-doped graphene nanoflakes. High specific capacitance in [N + R4 ]TFSI − based electrolytes (up to 167 F g −1 ). Significant contribution from pseudo-capacitance. High cycling stability in N + Et4 TFSI − and N + Bu4 TFSI − based electrolytes. Degradation in N + Me4 TFSI − because of the cation intercalation.